Who buffers income losses after job displacement? The role of alternative income sources, the family, and the state - Daniel Fackler; Eva Hank (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Using survey data from the German Socio-Economic Panel (SOEP) this paper analyses to what extent alternative income sources, reactions within the household context, and redistribution by the state attenuate earnings losses after job displacement. Applying propensity score matching and fixed effects estimations, we find high individual earnings losses after job displacement and only limited convergence. Income from self-employment slightly reduces the earnings gap and severance payments buffer losses in the short run. On the household level, we find substantial and rather persistent losses in per capita labour income. We do not find that increased labour supply by other household members contributes to the compensation of the income losses. Most importantly, our results show that redistribution within the tax and transfer system substantially mitigates income losses of displaced workers both in the short and the long run whereas other channels contribute only little.
Keywords: D10; I38; J63; J65; 330; job displacement; plant closure; household income; SOEP